Study on Porous Concrete: Permeability Analysis and Design Methodology of Pervious Concrete (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Pervious concrete or enhanced porosity concrete has a strictly gap graded coarse aggregate phase and little or no fine aggregates so as to facilitate the formation of an interconnected network of pores in the material. The material is designed with cementitious material content just enough to coat the coarse aggregate particles so that a configuration that allows the passage of water at a much higher rate than conventional concrete. The pervious concrete has many advantages that improves city environment, recharges the ground by rain water and could be used as pavement for light vehicles, pedestrian pathways, parking lots, also it reduces the tire pavement interaction noise etc. the effectiveness of a pervious concrete pavement depends as the intrinsic permeability of the mass, and normally this is defined by the porosity. It has been observed that porosity alone is an inadequate indicator of the permeability of pervious concretes, since the permeability depends on pore sizes, geometry and connectivity also. This paper presents a new method for determining the permeability of pervious concrete and provides design methodology to prepare pervious concrete based on experimental characteristics test values of pervious concretes.